Arsenic, the poison and poisoned groundwater of Bangladesh: A review - Uddin, Riaz; Saffoon, Nadia; Alam, Md Ashraful (International Current Pharmaceutical Journal, 2011)
DOI: http://dx.doi.org/10.3329/icpj.v1i1.9219 International Current Pharmaceutical Journal 2011, 1(1): 12-17